2004
DOI: 10.1074/jbc.m400585200
|View full text |Cite
|
Sign up to set email alerts
|

The Fourth Transmembrane Segment of the Na,K-ATPase α Subunit

Abstract: The Na,K-ATPase is a major ion-motive ATPase of the P-type family responsible for many aspects of cellular homeostasis. To determine the structure of the pathway for cations across the transmembrane portion of the Na,K-ATPase, we mutated 24 residues of the fourth transmembrane segment into cysteine and studied their function and accessibility by exposure to the sulfhydryl reagent 2-aminoethyl-methanethiosulfonate. Accessibility was also examined after treatment with palytoxin, which transforms the Na,K-pump in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…The same holds true for Gly 319 , which also has no direct interaction with ouabain in our model. The importance of this residue is also shown by the work of Horisberger et al (35) who found that replacement of this residue with a Cys resulted in a marked decrease in transport activity. Other amino acids present in M4 that have been implicated in ouabain binding are Leu 330 , Ala 331 , and Thr 338 (7).…”
Section: Discussionmentioning
confidence: 53%
“…The same holds true for Gly 319 , which also has no direct interaction with ouabain in our model. The importance of this residue is also shown by the work of Horisberger et al (35) who found that replacement of this residue with a Cys resulted in a marked decrease in transport activity. Other amino acids present in M4 that have been implicated in ouabain binding are Leu 330 , Ala 331 , and Thr 338 (7).…”
Section: Discussionmentioning
confidence: 53%
“…In view of the relationship between C2 and the ␣ subunit in the three-dimensional structure (Fig. 6A) glutathionylation may nevertheless contribute to regulation, for example by influencing the PEGL motif further down transmembrane helix 4 of the ␣ subunit that is critical for Na ϩ binding (34). Other effects of glutathionylation on FXYD/␣ interaction may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…All residues in TM9, Ile 953 29 and Gly 40 in FXYD7, the substitution of which has previously been shown to significantly affect the association efficiency with Na,KATPase (37), were not predicted to form favorable contacts by the docking. It remains to be shown whether substitution of these glycine residues could perturb correct folding of FXYD proteins, thus limiting complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein Modeling-Based on our previous homology model of the Bufo Na-K-ATPase (29) in the E1 conformation, a model of the FXYD7/ Na-K-ATPase complex was built using an evolutionary algorithm. The details of the calculations will be presented separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation